Modified Charge Transport Model Under High-Frequency Unipolar Square Wave Voltage - Xie, Jianxiang; Yan, Shen; Shi, Mingchen; Zhang, Yiyi; Liu, Jiefeng (Frontiers in Materials, 2022)
As the main insulation material of the power electronic transformer (PET), polyimide (PI) is easy to accumulate space charge under the continuous high-frequency pulse voltage, which will threaten the operation of PET and cause electric field distortion. At present, the microscopic mechanism of charge transport under high-frequency voltage is unclear. Numerical simulation is an effective method to explore the transport characteristics of space charge. The simulation of charge transport under DC voltage is mainly based on the bipolar charge transport (BCT) model. However, the charge transport behaviors under high-frequency pulse voltage cannot be simulated by the traditional models accurately. Given this, based on the BCT model, the High-Frequency Voltage Charge Transport (HFCT) model is proposed, considering nonlinear charge mobility of the polymer and the effect of the frequency. Finally, the space charge and electric field distribution under square pulse wave voltages with different rising times are simulated based on the HVCT model, concluding that the reduction of rising time will promote the accumulation of space charge. In view of this, the HVCT model is expected to optimize the insulation design of PET and provide a reference for the dynamic simulation of space charge.